Visitas técnicas: um processo de "conciliação" escola-empresa - Lima, Anselmo Pereira de (2008)
The objective of this study is to apprehend and reflect on linguistic and discoursive aspects of the teaching and learning work in the field of high school vocational education, by means of the description of Technical Visits from the standpoint of discourse and activity genres. In these educational events, a teacher and his students go to a company workshop to check out in practice that which they have studied only in theory in a vocational training center. One of the workers of the visited workshop, who has been named collaborator by the teacher-researcher, receives the group and presents the work done in it, which gives place to teacher-collaborator-students interactions. A survey of the history of vocational education teaching methodologies in Brazil suggested that it has always been difficult to put the educational and the industrial spheres together. This suggestion led to the hypothesis that this historical difficulty should somehow manifest itself in the process of making Technical Visits. In order to check this hypothesis, a sequence of four of these events was recorded audiovisually and one of them was transcribed in its entirety for analysis. The research theoretical basis comes from the Language Studies (Bakhtin and his Circle), from Linguistics (Benveniste), from the Ergonomy of Teacher Activity (Amigues), from the Historicocultural Psychology (Vigotski and Léontiev) and from Work Psychology (Clot). By observing the transcription, a survey of the phases of the Technical Visits and of the stages of each one of these phases was carried out. The interdisciplinary analysis of the sequence of these phases and stages allowed the identification of the establishment and maintenance of a certain generic structure in the unfolding of the event, which after a specific moment gets unstable in order to restabilize itself in a different way. It was possible to come to the conclusion that there is a link between this process of genre instabilization and restabilization and the difficulty to put the educational and the industrial spheres together. As the Technical Visits are repeated, this difficulty is gradually overcome and the discourse and activity genre progressively stabilizes itself, until it acquires a relatively stable form. According to the thesis developed in this study, this process takes place by means of a Regulating Activity in a teacher-collaborator-students tense interaction. The relevance of this research, among other factors, is due to the lack of researches and publications about Technical Visits, a didactic and pedagogical resource so often employed in high school or college vocational programs